Exploring children breakfast habits using Zoom8-questionnaire: Results from the I-MOVE Study. (20th October 2021) - Scrimaglia, S; Esposito, F; Sanmarchi, F; Marini, S; Masini, A; Melis, A; Sacchetti, R; Dallolio, L
Abstract: Background: Scientific evidence widely argues that consuming breakfast daily is considered a good habit which positively affects health and academic performance, especially in children. In order to be adequate, according to national requirements, breakfast should include a portion of milk or yogurt and one grain based product, providing about 15-20% of the daily recommended energy intake. The aim of this study was to analyse breakfast habits in a convenience sample of primary school children inside the Imola Active Breaks Study. Methods: A cross-sectional study was conducted in a sample of children, aged 6-10, recruited in a primary school of Imola (Emilia Romagna region, Italy). The Zoom8 self-reported questionnaire, which investigates dietary habits and lifestyle aspects were administered to parents to explore the children's breakfast habits. Results: A total of 155 children were recruited in November 2019. Breakfast was consumed daily by 117 children (75%), 4-6 times/week by 12 (7%), 2-4 times/week by 4 (3%), and 22 (14%) did not answer. Concerning dairy products' consumption: 50 (32%) children reported milk or yogurt, 47 (30%) milk, 6 (4%) yogurt, 9 (6%) neither of them and 43 (28%) gave no answer. Mostly all the children consumed at least one of these products: biscuits, cakes, croissants, industrial snacks or cereals. 108 children (70%) recognised that the consumption of a dairy and a carbohydrate product represent an adequate breakfast. Conclusions: The findings suggested that the majority of children consumed one grain based product for breakfast, but most of them were high in sugar and fat content (industrial snacks and croissants). Still not every child had breakfast daily nor had a portion of a dairy product. Measurements should be taken to avoid skipping breakfast and to promote a more balanced breakfast. It would be advisable to analyse in detail the frequency of consumption of each food group and their energy intake. Key messages: Breakfast consumption positively affects children's health and academic performance. Health Promotion should stimulate daily consumption of breakfast and improve its quality and energy intake.